Pendampingan Strategi Promosi dan Diversifikasi Produk Ubi Kremes pada UMKM Rumahan Snack Kelurahan Dalung Cipocok Jaya: Pengabdian - Azizah, Oktafia; Wahyu Wiguna; Sukma Pratama; Irwanto; Alifah; Jane (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
MEs are a key pillar of the national economy, playing a significant role in creating jobs and improving community welfare. However, many MSMEs face challenges in expanding their markets, particularly in promotion and product innovation. This community service activity aims to improve the competitiveness of the